2013
DOI: 10.1097/mao.0b013e31829763a7
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants to Treat Deafness Caused by Vestibular Schwannomas

Abstract: Patients with unilateral VS (sporadic or those affected with NF2) whose tumor status was stable, benefited from cochlear implantation in their tumor-affected ear. Patients who had radiotherapy also benefited from CI, but their outcomes were variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…Lloyd et al [33] have recently published results of this type of approach using either retrosigmoid or translabyrinthine surgery and have demonstrated that it is possible to gain significant benefit from a cochlear implant in the majority of patients. It seems that cochlear implantation alone in patients with profound hearing loss and stable tumours is a further option and has been shown to produce effective hearing rehabilitation with post implantation speech discrimination scores of around 60 % [34,35]. Outcomes of cochlear implantation following growth stabilization with radiosurgery are poorer, however [34,35].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lloyd et al [33] have recently published results of this type of approach using either retrosigmoid or translabyrinthine surgery and have demonstrated that it is possible to gain significant benefit from a cochlear implant in the majority of patients. It seems that cochlear implantation alone in patients with profound hearing loss and stable tumours is a further option and has been shown to produce effective hearing rehabilitation with post implantation speech discrimination scores of around 60 % [34,35]. Outcomes of cochlear implantation following growth stabilization with radiosurgery are poorer, however [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…It seems that cochlear implantation alone in patients with profound hearing loss and stable tumours is a further option and has been shown to produce effective hearing rehabilitation with post implantation speech discrimination scores of around 60 % [34,35]. Outcomes of cochlear implantation following growth stabilization with radiosurgery are poorer, however [34,35]. Finally, ABI is an option if a tumour requires removal and cochlear nerve preservation is not possible [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a cochlear implant can be a valid therapeutic option only if cochlear nerve function is preserved in the first place. There are several reports, which show how cochlear implantation can be an effective solution for hearing restoration in patients with VS either as hearing loss treatment without removing the tumour 3 or after VS resection, although they deal with severe bilateral hearing loss patients affected by neurofibromatosis 2 or by sporadic VS in the only hearing ear 4 5 . The presented case was treated as a single-sided deafness in order to relieve the patient's severe tinnitus and to restore binaural hearing.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, CI may provide new options for hearing restoration with limited morbidity in this circumstance [4,17]. For patients with VS in the only hearing ear, significant hearing deterioration on the tumor side with no evidence of tumor growth is an indication that ipsilateral CI is likely to be successful, given that nearly two-thirds of tumors, especially stable ones, do not grow [18,19].…”
Section: Discussionmentioning
confidence: 99%